Comparison of various method of fetal birth weight estimation in term pregnancy - Prajapati, Darshit G.; Patel, Riddhi M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Introduction: Knowledge of fetal weight in utero is vital for the obstetrician in deciding whether or not to deliver the fetus as well as in fixing the mode of delivery. Both low birth weight and excessive fetal weight at delivery are associated with increased risk of newborn complications during labor and the puerperium. Various clinical formulae like Johnson’s formula & Dare’s formula and USG are in use for fetal weight estimation. Objectives: The aim of this study was to assess the fetal weight in term pregnancies by various methods- Dare’s formula, Johnson’s formula and Hadlock’s formula using ultrasound, and to compare the methods after knowing the actual weight of the baby after birth. Methods: It is a prospective observational study of 227 women at term pregnancy at GMERS medical college & Hospital, sola , Ahmedabad from April 2014 to April 2016. The formulas used in this study are: Johnson’s formula, Dare’s formula and Hadlock-4 formula using ultrasound. Result: Results vary in terms of accuracy with various methods employed for estimating the fetal weight. This study showed that Hadlock-4 was the best indicator among all other methods assessed followed by Dare’s formula. Conclusion: Whenever the Facility is available, Ultrasound is the best method for birth weight assessment. Dare’s formula is an inexpensive method for screening for fetal growth restriction. It continues to be used in many countries on large scale because of its low cost, ease of use, and need for little training as the setup for ultrasonographic evaluation is not readily available in rural setups.